Impact of "Learn the Signs. Act Early." Materials on Parental Engagement and Doctor Interaction Regarding Child Development. Issue 9 (December 2018) - Gadomski, Anne M.; Riley, Moira R.; Scribani, Melissa; Tallman, Nancy
ABSTRACT: Objective: To measure the effectiveness of the "Learn the Signs. Act Early." (LTSAE) educational materials in increasing parent engagement in developmental monitoring during well-child visits. Methods: Exit surveys and analysis of audio-taped well-child visits were compared pre- versus post-LTSAE exposure. Before the LTSAE, parents were exposed to usual pediatric clinic developmental surveillance practices. After the LTSAE, parents received LTSAE materials before well-child visits, received age-specific LTSAE checklists at the clinic visit, and were exposed to LTSAE posters in examination rooms. Pediatricians attended a didactic session on developmental screening and LTSAE materials. Children evenly distributed among the ages of 2, 4, 6, 9, 12, and 18 months and 2 and 3 years were consecutively recruited at their well-child visits. After the visit, all parents completed exit surveys that assessed 5 a priori outcomes: milestone awareness, level of concern if the child is late in reaching a milestone, likelihood of bringing up a concern to the doctor, level of confidence in knowing what to do if concerned, or talking about child development during the visit. A 25% visit subsample was audio-taped, transcribed, and coded for parental engagement and nurse/doctor response to parental concern. Results: No demographic differences were found between the 181 parents enrolled before the LTSAE and 182 after the LTSAE. LTSAE exposure was significantly higher after the LTSAE ( p < 0.0001). After the LTSAE, parent awareness of the number of milestones increased ( p = 0.03). Audiotape analysis showed that parents were more engaged in discussions about development post-LTSAE versus pre-LTSAE. Conclusion: The LTSAE may improve developmental surveillance by increasing parent's awareness of and discussion about milestones.